‘Among predators’: the place of humans, Iberian lynx and other wild carnivores - Lopes-Fernandes,Margarida (2022)
Abstract Using an ethnoecological approach we studied perceptions, empirical classifications and practices towards wild predators in Portuguese protected areas. Results from 131 semi-structured interviews allowed the analysis of classification, criteria used by key actors and the understanding of an emic perspective on the differentiation of the natural world. Further analysis and data from observation reveal local ecological knowledge associated with characteristics of carnivores. Oral memories about coexistence of humans with wolf and lynx in the late 20thcentury in Baixo Alentejo are described. Humans are recognized as one of the predators in a complex and apparent dualistic view of domestic and wild realms associated with past control practices. In its reintroduction area the threatened Iberian lynx raised much interest locally and after being classified as an “outsider” it became the centre of touristification. This case study characterizes a European rural scenario “among predators” where nature conservation is facing challenges and Anthropology has an opportunity of interdisciplinary application.